Kontroversi Dakwah Gus Miftah dalam Diskursus Digital: Analisis Sosio-Kultural Respon Nitizen - Fikri, Mursyid (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
The controversy surrounding Islamic preaching (da'wah) involving a prominent religious figure in Indonesia, Miftah Maulana Habiburrahman, well known as Gus Miftah, arose from his use of the word